Content and Quality of Motor Initiatives in the Support of People With Profound Intellectual and Multiple Disabilities. Issue 4 (9th December 2019) - van Alphen, Helena J. M.; Waninge, Aly; Minnaert, Alexander E. M. G.; van der Putten, Annette A. J.
Abstract: Motor activation is rarely integrated into the support of people with profound intellectual and multiple disabilities (PIMD), which might be the result of the limited evidence‐based knowledge in this field. Practitioners have recently been developing several motor initiatives for people with PIMD, but it remains unclear about what core elements the motor initiatives actually consist of and to what level of quality it is implemented in practice. This study aims to offer an overview and analysis of the content and quality of motor initiatives actually in use for people with PIMD. Motor initiatives were explored by asking practitioners to complete an online inventory form. Documents, expert knowledge, and observations were used to collect data about the characteristics of the motor initiatives. The quality of the motor initiatives which met our eligibility criteria, was analyzed on the basis of the level of evidence for their effectiveness. The inventory yielded 118 motor initiatives of which 17 met the eligibility criteria. We identified four motor initiatives reflecting an approach to motorically activate people with PIMD within various activities, three including power‐assisted exercises, three with aquatic exercises, two frameworks which integrated motor activities into their daily programs, two methods which included small‐scale activities, two rhythmic movement therapies, and one program including gross motor activities. We found limited indications for descriptive evidence from 17 initiatives, limited or no indications for theoretical evidence from 12 and five initiatives respectively, and none of the initiatives provided a causal level of evidence for effectiveness. A wide variety of motor initiatives is used in current practice to activate persons with PIMD, although their effectiveness is actually unproven. Science and practice should cooperate to develop an evidence‐based understanding to ensure more evidence‐based support for the motor activation of people with PIMD in the future.